1998
DOI: 10.1074/jbc.273.42.27573
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the ATP- and GTP-specific Succinyl-CoA Synthetases in Pigeon

Abstract: Two succinyl-CoA synthetases, one highly specific for GTP/GDP and the other for ATP/ADP, have been purified to homogeneity from pigeon liver and breast muscle. The two enzymes are differentially distributed in pigeon, with only the GTP-specific enzyme detected in liver and the ATP-specific enzyme in breast muscle. Based on assays in the direction of CoA formation, the ratios of GTP-specific to ATP-specific activities in kidney, brain, and heart are ϳ7, 1, and 0.1, respectively. Both enzymes have the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 27 publications
1
57
0
Order By: Relevance
“…The same ␣ subunit is found in both A-SCS and G-SCS enzymes (1). Northern blots revealed a single transcript of 1.5 kb with the strongest expression of ␣ observed in heart followed by kidney, liver, and testis.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The same ␣ subunit is found in both A-SCS and G-SCS enzymes (1). Northern blots revealed a single transcript of 1.5 kb with the strongest expression of ␣ observed in heart followed by kidney, liver, and testis.…”
Section: Resultsmentioning
confidence: 89%
“…Both enzymes are located in the matrix of mitochondria, where they could participate in the citric acid cycle. We previously found that G-SCS is by far the predominant enzyme detected by enzyme assay in pigeon liver, whereas A-SCS predominates in pigeon breast muscle (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are 2 isoforms of SCS, the GTP-specific (G-SCS) and ATP-specific isoforms (A-SCS) (33). Recently, it has been shown that the 2 isoforms of SCS contain the identical α subunit, although they differ in their β subunits, indicating that the β subunit determines the specificity of nucleotide binding (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of A-SCS in animals began with its purification from blowfly thorax (7), and its detection in tissue homogenates (8,9). We then purified A-SCS in pigeon breast muscle and G-SCS in liver, demonstrated that each enzyme is highly specific for its nucleotide, and showed that both contain alpha-and beta-type subunits (10). Although the same alpha subunit was found in both enzymes, the beta subunits were only 53% identical in sequence (11) and thus confer nucleotide specificity.…”
Section: A David O Lambeth E-mail: Dlambeth@medicinenodak Edumentioning
confidence: 99%